Biological, as opposed to classic antipsoriatic drug or apremilast, treatment mitigates the risk of death and cardiovascular disease in psoriasisResearch in context - Khalaf Kridin; Katja Bieber; Artem Vorobyev; Eva Lotta Moderegger; Henning Olbrich; Marlene A. Ludwig; Bernard Gershater; Gema Hernandez; Henner Zirpel; Diamant Thaci; Ralf J. Ludwig (EBioMedicine)
Summary: Background: Cardiovascular comorbidity increases morbidity and mortality in psoriasis. Systemic treatments, particularly biologics, are effective in alleviating skin and joint inflammation. Conversely, the impact of systemic therapy on cardiovascular disease risk and mortality in psoriasis remains uncertain. Methods: Impact of systemic treatments on all-cause mortality and cardiovascular disease risk in psoriasis patients' electronic health records (EHRs) from TriNetX was assessed. Treatment categories included apremilast, IL-17 inhibitors (IL-17i), IL23i, TNFi, and classic antipsoriatic drugs. Index event was the first prescription of each treatment, requiring a two-year continuous treatment with exclusion of other systemic antipsoriatic drugs. Propensity-score matching was used to improve comparability. Sensitivity analyses ensured study robustness. Findings: In descriptive analysis, all-cause mortality rates were 0.61% (classic antipsoriatics, n = 7929), 0.91% (apremilast, n = 1101), 0.00% (IL17i, n = 677), 0.81% (IL23i, n = 1242), and 0.20% (TNFi, n = 6468). Major adverse cardiac events (MACE) were documented in 8.49% (classic antipsoriatics), 5.14% (apremilast), 2.99% (IL17i), 2.09% (IL23i), and 3.74% (TNFi) EHRs. Propensity-score matching showed all-cause mortality rates of 0.23% for any biologic vs. 0.49% for classic antipsoriatics or apremilast, resulting in an HR of 2.21 (95% CI 1.21–3.71, p = 0.0073). MACE risk was also higher with classic antipsoriatics or apremilast (HR 1.66, CI 1.43–1.93, p < 0.0001). The majority of findings were consistent across all four sensitivity analyses. No significant differences in all-cause mortality or MACE risk were observed among biologics. Interpretation: Biological treatment, as opposed to classic antipsoriatic drugs or apremilast, reduces risk of death and cardiovascular disease in psoriasis. Prospective trials are required to validate these findings. Funding: DFG: EXC 2167 and LU 877/25-1. State of Schleswig Holstein: Excellence-Chair Program.